Categorisation of Isolate Ideas: A Comparative Study - Seetharama, S. (Journal of Information and Knowledge, 1972)
The emergence of the concept of the Fundamental Categories - Personality, Matter, Energy, Space and Time - first in an incipient form and lalei in a full-fledged form is traced. The method of identification, and the postulates and principles for the sequence of the fundamental categories are briefly discussed. A review of the various attempts at the postulation of a conceptual structure of subjects in order to facilitiate the helpful arrangement of subjects embodied in documents, is presented. The concept of the Five Fundamental Categories in Ranganathan’s General Theory of Library Classification if, relatively more versatile and comprehensive.